I can only imagine 2 [videorecording (DVD)] - Kebbel, Arielle, 1985-; Ventimiglia, Milo, 1977-; Quaid, Dennis; Finley, J. Michael, 1988-; Skelton, Sophie, 1994-; Adkins, Trace; Dell, Sammy; McCorkle, Brent (Lionsgate, 2026)
After the breakout success of the song 'I Can Only Imagine,' MercyMe's Bart Millard has it all until fame starts to cost him what matters most. When hopeful newcomer Tim Timmons joins the band for their biggest tour yet, he unknowingly brings renewed gratitude to Bart's life. Based on the true story behind the hit single 'Even If,' I Can Only Imagine 2 is the inspiring next chapter of faith, family, and finding God in the fire.